Detailed surface analysis of V‐defects in GaN films on patterned silicon(111) substrates by metal–organic chemical vapour deposition. Corrigendum. Issue 1 (27th January 2020) - Gao, Jiang-Dong; Zhang, Jian-Li; Zhu, Xin; Wu, Xiao-Ming; Mo, Chun-Lan; Pan, Shuan; Liu, Jun-Lin; Jiang, Feng-Yi
Abstract : An error in the article by Gao, Zhang, Zhu, Wu, Mo, Pan, Liu & Jiang [ J. Appl. Cryst. (2019), 52, 637–642] is corrected. Abstract : An error in the article by Gao, Zhang, Zhu, Wu, Mo, Pan, Liu & Jiang [ J. Appl. Cryst. (2019), 52, 637–642] is corrected.